2017
DOI: 10.1007/s13595-017-0681-7
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the structure and function of the understory plant communities to precipitation reduction across forest ecosystems in Germany

Abstract: & Key message Understory plant communities are essential for the recruitment of trees making up future forests. Independent of plant diversity, the understory across different forest ecosystems shows considerable physiological acclimation and structural stability towards drought events, which are expected to occur more frequently in future. & Context Understory plant communities are essential for the recruitment of trees making up the future forest. It is so far poorly understood how climate change will affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 78 publications
2
12
0
Order By: Relevance
“…In the study by Ozolinčius et al (2009), loss of ground cover was associated with a 20% decrease in also the Shannon index, while we found that the negative impact was on plot species richness but not on Shannon-diversity. These results support Felsmann et al (2018) who found a tendency for lower species richness vs. considerable stability in the structure (diversity and composition) of understorey community of beech and conifer forests exposed to drought treatments for 18 months. In that experiment diversity was not affected thanks to the high plasticity of understorey plants to moderate reduction of soil water content (Felsmann et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the study by Ozolinčius et al (2009), loss of ground cover was associated with a 20% decrease in also the Shannon index, while we found that the negative impact was on plot species richness but not on Shannon-diversity. These results support Felsmann et al (2018) who found a tendency for lower species richness vs. considerable stability in the structure (diversity and composition) of understorey community of beech and conifer forests exposed to drought treatments for 18 months. In that experiment diversity was not affected thanks to the high plasticity of understorey plants to moderate reduction of soil water content (Felsmann et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Although the many drivers of global change are known to affect in multiple and interactive ways this forest layer, the potential impacts of extreme climate events have been overlooked in the recent literature. Frequency and duration of drought and heat episodes are indeed among the potential drivers of direct and overstorey-mediated changes in the structure of understorey communities (Archaux and Wolters, 2006;Felsmann, et al, 2018). Since current climate projections predict strong reductions of summer precipitation and an increase in the occurrence of drought periods all over Europe (IPCC, 2012;, there is a need for interdisciplinary research initiatives on the short-term consequences of such events on forest biodiversity (Archaux and Wolters, 2006;Felsmann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, hydrologists recognize BROOK90 as a useful tool for studies of the water balance for small plots in mainly forested regions (i.e., from the most recent studies [25][26][27][28][29]). Therefore, it has been used in research, teaching, and water management, and also because of its ability to gain reasonable results even under changing climate conditions [20].…”
Section: Short Introduction To the Original Brook90 Modelmentioning
confidence: 99%
“…A reduction in precipitation, especially drought, can limit the regeneration potential and composition of plants because almost all species are very susceptible to environmental factors at the seedling stages [8,13,14]. Osem et al [12] reported that species composition at regeneration stages varied in regions with an annual rainfall of 300 to 900 mm.…”
Section: Introductionmentioning
confidence: 99%